Development of a Stability-Indicating High Performance Liquid Chromatographic Method for the Analysis of Topiramate and Dissolution Rate Testing in Topiramate Tablets - Mohammadi, Ali; Rezanour, Nasrin; Ansari, Mahdi; B. Walker, Roderick (Asian Journal of Chemistry, 2010)
A stability-indicating high performance liquid chromatographic (HPLC) method was developed and validated for the quantitation and dissolution determination of topiramate in tablet dosage forms. An isocratic separation was achieved using a phenyl column with a flow rate of 1 mL/min using UV detection at 264 nm. Topiramate has low UV absorbtivity and was subjected to derivatization with 9-fluorenylmethyl chloroformate (FMOC-Cl). The mobile phase for the separation consisted of acetonitrile: 50 mM sodium dihydrogen phosphate (NaH2PO4) containing 3 % v/v triethylamine (pH 2.8) in a 48:52 v/v ratio. Topiramate was subjected to oxidation, hydrolysis, photolysis and heat for the purposes of stress testing. Separation was achieved for the parent compound and all the degradation products in an overall analytical run time of approximately 15 min with the parent compound topiramate eluting at approximately 9.2 min. The method was linear over the concentration range of 1-100 μg/mL (r = 0.9996) with limits of quantitation and detection of 1 and 0.3 μg/mL, respectively.